2016
DOI: 10.1371/journal.pntd.0004863
|View full text |Cite|
|
Sign up to set email alerts
|

Low Prevalence of Conjunctival Infection with Chlamydia trachomatis in a Treatment-Naïve Trachoma-Endemic Region of the Solomon Islands

Abstract: BackgroundTrachoma is endemic in several Pacific Island states. Recent surveys across the Solomon Islands indicated that whilst trachomatous inflammation—follicular (TF) was present at levels warranting intervention, the prevalence of trachomatous trichiasis (TT) was low. We set out to determine the relationship between chlamydial infection and trachoma in this population.MethodsWe conducted a population-based trachoma prevalence survey of 3674 individuals from two Solomon Islands provinces. Participants were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
76
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

6
3

Authors

Journals

citations
Cited by 42 publications
(84 citation statements)
references
References 74 publications
6
76
2
Order By: Relevance
“…This is concordant with our previous data, which suggested that although ocular Ct strains are present in the Solomon Islands, they are rare 3 . This contrasts with the data from Kiritimati Island, where we saw that there was a substantial year-on-year increase in age specific seropositivity ( Figure 3B).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is concordant with our previous data, which suggested that although ocular Ct strains are present in the Solomon Islands, they are rare 3 . This contrasts with the data from Kiritimati Island, where we saw that there was a substantial year-on-year increase in age specific seropositivity ( Figure 3B).…”
Section: Discussionsupporting
confidence: 93%
“…Whilst measures for trachoma elimination have already been deployed in Temotu and Rennell & Bellona, we have previously noted that TI, ocular Ct infection and late-stage disease (TT) are rare 3 . If the village level findings of the current study were replicated throughout the district, then TF would still be sufficiently prevalent to warrant continued intervention.…”
Section: Discussionmentioning
confidence: 99%
“…In the Solomon Islands, the prevalence of TF is sufficient to warrant MDA but the prevalence of trachomatous trichiasis (TT) suggests trachoma may not pose a significant public health problem. A recent trachoma survey in a treatment-naïve population of the Solomon Islands estimated 26% of 19-year-olds to have TF but, surprisingly, conjunctival Ct infection was detected in only 1.3% of that age group (3). Whilst Ct infection is not always detectable in TF cases (4, 5), infection prevalence in the Solomon Islands is far lower than is seen in other countries with similar TF prevalence (3).…”
Section: Introductionmentioning
confidence: 99%
“…All these reports have no description of intense inflammatory trachoma or more severe trachoma cases, likely due to the low prevalence of trachoma in these areas. Given that presence of clinical signs of trachoma such as conjunctival follicles might be due to non-chlamydial causes in low prevalence settings or regions (Butcher et al, 2016), the use of a specific nucleic acid amplification test or preferably whole-genome sequencing is recommended in order to establish or rule out the cause of disease.…”
Section: Discussionmentioning
confidence: 99%